Estimation of Person Ability under Rapid and Effortful Responding - Georgios Sideridis; Maisa Alahmadi (Journal of Intelligence, 2022)
The goal of the present study was to extend earlier work on the estimation of person theta using maximum likelihood estimation in R by accounting for rapid guessing. This paper provides a modified R function that accommodates person thetas using the Rasch or 2PL models and implements corrections for the presence of rapid guessing or informed guessing behaviors. Initially, a sample of 200 participants was generated using Mplus in order to demonstrate the use of the function with the full sample and a single participant in particular. Subsequently, the function was applied to data from the General Aptitude Test (GAT) and the measurement of cognitive ability. Using a sample of 8500 participants, the present R function was demonstrated. An illustrative example of a single participant, assumed to be either a rapid responder or a successful guesser, is provided using MLE and BME. It was concluded that the present function can contribute to a more valid estimation of person ability.